STUDENT FEEDBACK SURVEY ON USING FLEXIBLE PAVEMENT DESIGN TOOL (FLEXIPAVD) IN LEARNING FLEXIBLE PAVEMENT DESIGN - Shahreena Melati Rhasbudin Shah1=; Tey Li Sian; Zanariah Abd Rahman, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study presents the findings from a survey conducted to gather student feedback on the efficacy and user experience of a teaching and learning tool for flexible pavement design, namely FlexiPavD. In most Malaysian universities, the Highway and Traffic Engineering course syllabus includes the design of flexible pavements. The student needs to go through a manual (more than 30 pages) to assist them in designing a flexible pavement. This process may result in human error in addition to wasting money, time, and paper. With this in mind, we develop a tool using Microsoft Excel to help assist students in carrying out the design process anytime and anywhere from hp, tablet, laptop, or pc. However, no matter how well the tool is developed, it will serve no purpose if the student does not benefit from it. Therefore, the survey aimed to evaluate the tool's impact on students' learning process and overall satisfaction. Data were gathered from a diverse cohort of 50 undergraduate students through an online survey platform to ensure ease of access and involvement. The results indicate a generally positive reception of the tool, with 90% of respondents being satisfied with the design tool, and 10% feeling neutral. It is concluded that the tool is pertinent to the teaching and learning process based on the fact that 92% of students concur that FlexiPavD is helpful for their learning process in flexible pavement design.